Developing a Promotional Video Script for Green Paradise Resort in Pagar Alam as a Tourism Destination - Anggi Nur Afni (Holistics (Hospitality and Linguistics) : Jurnal Ilmiah Bahasa Inggris, 2025)
This study aims to develop an English-language promotional video script for Green Paradise Resort as a tourism destination in Pagar Alam, South Sumatra. The research employed a qualitative approach combined with a Research and Development (R&D) method based on the Plomp model, which includes preliminary study, design, realization, evaluation, and implementation. Data were collected through literature study, direct observation, and interviews with the resort owner to identify promotional needs, destination characteristics, and storytelling elements. The script was developed using a structured narrative framework consisting of a hook, introduction, body, and closing, and incorporated the 5A tourism concept: Attraction, Accessibility, Amenity, Activities, and Awareness. The realization stage resulted in an English promotional video script highlighting the resort’s natural attractions, facilities, eco-tourism values, and cultural experiences. The script was validated by four experts in script content, video production, Indonesian language, and English language. Expert feedback led to revisions that improved clarity, narrative flow, emotional appeal, and audiovisual suitability. The final product is a validated promotional video script suitable for digital tourism promotion and effective in enhancing destination branding, particularly for international audiences. Keywords: destination branding, tourism promotion, video scriptwriting DOI: https://doi.org/10.5281/zenodo.18228150